2017
DOI: 10.1002/polb.24321
|View full text |Cite
|
Sign up to set email alerts
|

Temperature compensation of dye doped polymeric microscale lasers

Abstract: In this article, a new technique for building temperature compensated microscale lasers that are based on the morphology dependent resonances phenomenon is presented. The dome shaped resonator is made with a mixture of NBA 107 UV curable polymer and rhodamine 6 g dissolved in ethanol solution. Since polymers usually exhibit linear thermal expansion and thermo-optic coefficients that are opposite in sign but similar in order of magnitude, it is possible to compensate for temperature over the dome shaped resonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…The average Q factor value was 2.9 × 10 4 and was comparable with the Q factor found in microlasers fabricated with other techniques. The quality factor Q is a measure of how resolute a sensor based on optical microlasers [1][2][3][4][5]9,10]. This means that the fabrication method did not affect the quality factor of the microlasers, or that the variation of the Q factor was below the instrument resolution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average Q factor value was 2.9 × 10 4 and was comparable with the Q factor found in microlasers fabricated with other techniques. The quality factor Q is a measure of how resolute a sensor based on optical microlasers [1][2][3][4][5]9,10]. This means that the fabrication method did not affect the quality factor of the microlasers, or that the variation of the Q factor was below the instrument resolution.…”
Section: Resultsmentioning
confidence: 99%
“…Microscale circular structures that enable whispering gallery modes (WGMs) have been employed as passive and active elements for different applications such as non-linear optics, low threshold microlasers, filters, and sensors [1][2][3][4][5][6][7][8][9][10][11][12]. Different materials have been used for the fabrication of these organized microstructures such as polymers, crystals, and other exotic materials [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…This can be obtained by optimizing the tubular axial confinement in the future. 17 It has been reported that there is a negative thermal expansion coefficient in graphene 58 and the thermo-optic effect in R6G-doped microcavities, 59 which may influence the effective refractive index of the optoplasmonic cavity and contribute to the extra mode shift. Here, the extra mode shift induced by thermal effect can be negligible due to the relatively low laser power (2 mW) and good thermal conductivity of the ultrathin tube wall.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A change of the pressure applied to the internal wall of the pipe causes a mechanical strain on the perimeter of the resonator and, as a consequence, a shift of optical modes occurs as explained in detail in section 2 and section 3. Due to their high resolution, high sensitivity, and small size, WGM sensors have been developed to detect many different physical quantities including electric fields [13][14][15][16] , magnetic fields 15,17,18 , wall shear stress [19][20][21] , temperature [22][23][24] , applied loads 25,26 , displacement [27][28][29][30][31] , and radiant energy 32 among others. Section 2 of this paper explains how the WGM phenomenon is utilized in sensing applications.…”
Section: Introductionmentioning
confidence: 99%